Targeting Myc Interacting Proteins as a Winding Path in Cancer Therapy - Yihui Zhou; Xiaomeng Gao; Meng Yuan; Bo Yang; Bo Yang; Qiaojun He; Qiaojun He; Qiaojun He; Ji Cao; Ji Cao; Ji Cao (Frontiers Media S.A., 2021)
MYC, as a well-known oncogene, plays essential roles in promoting tumor occurrence, development, invasion and metastasis in many kinds of solid tumors and hematologic neoplasms. In tumors, the low expression and the short half-life of Myc are reversed, cause tumorigenesis. And proteins that directly interact with different Myc domains have exerted a significant impact in the process of Myc-driven carcinogenesis. Apart from affecting the transcription of Myc target genes, Myc interaction proteins also regulate the stability of Myc through acetylation, methylation, phosphorylation and other post-translational modifications, as well as competitive combination with Myc. In this review, we summarize a series of Myc interacting proteins and recent advances in the related inhibitors, hoping that can provide new opportunities for Myc-driven cancer treatment.